KAJIAN FILOSOFI TRADISI MEGÉBÉG-GÉBÉGAN GODÉL DALAM UPACARA BHUTA YAJÑA DI DESA ADAT DHARMAJATI TUKADMUNGGA KECAMATAN BULELENG KABUPATEN BULELENG - Ketut Sriwahyuni; I Wayan Gata; I Putu Ariasa Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The Megébég-gébégan godél tradition is a tradition that is carried out by grabbing or pulling the godél's head. This tradition is carried out once a year, namely one day before the Nyepi holiday. Looking at this background, the problem can be formulated as follows: 1) What is the basis of the megébég-gébégan godél tradition in the Dharmajati Tukadmungga Traditional Village, Buleleng District, Buleleng Regency? 2) What is the Megébég-gébégan godél traditional system in the Dharmajati Tukadmungga Traditional Village, Buleleng District, Buleleng Regency? 3) What is the meaning of the philosophy of the Megébég-gébégan godél tradition in the Dharmajati Tukadmungga Traditional Village, Buleleng District, Buleleng Regency? The theories used include: 1) Religious theory, 2) Structural functional theory, and 3) Symbol theory. The methods used to collect data are: observation method, interview method, and document study method. The results obtained from this research are: 1) The Megébég-gébégan godél tradition is based on a historical basis, a mythological basis, a religious basis, and a social basis. 2) This traditional system is: (1) The place of implementation is at the great intersection (catus pata) and The implementation time is once a year, the day before the Nyepi holiday, (2) The means of implementing the tradition are godél and using banten, the implementers of the megébég-gébégan godél tradition are: the Dharmajati Tukadmungga Traditional Village Community, Jro Mangku Kahyangan Tiga, and Sarati Banten. The process of carrying out the bhuta yajña ceremony begins with mepepade, prayers at Pura Dalem, followed by the tawur grand senga and the megébég-gébégan godél tradition, 3) The meanings contained in the Megébég-gébégan godél tradition are: the meaning of philosophy, the meaning of Tri Hita Karana, the meaning of togetherness, ethical meaning, meaning, and significance of cultural preservation Keywords: Megébég-gébégan Godél Tradition, Philosophical Studies